2011
DOI: 10.3109/00048674.2011.570309
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Obesity in Childhood and Risk of Mental Disorder: a 20-Year Cohort Study

Abstract: Childhood overweight may increase risk for mood disorder in adulthood, especially among overweight girls who become obese women. These results suggest that prevention of childhood overweight is equally important in both sexes for reducing risk of diagnosed mood disorder in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
103
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(114 citation statements)
references
References 33 publications
8
103
0
3
Order By: Relevance
“…This finding was also supported in a review by Berkowtiz and Fabricatore (2011). Childhood overweight and obesity is associated with an increased risk of mood disorder in adulthood (Sanderson et al, 2011), and higher rates of overweight and obesity have been observed in medication-naïve patients with bipolar disorder (Maina et al, 2008).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…This finding was also supported in a review by Berkowtiz and Fabricatore (2011). Childhood overweight and obesity is associated with an increased risk of mood disorder in adulthood (Sanderson et al, 2011), and higher rates of overweight and obesity have been observed in medication-naïve patients with bipolar disorder (Maina et al, 2008).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…31 Moreover, several longitudinal studies have revealed that children's BMI levels track to adulthood, 26,[32][33][34] with approximately 70% of children who are obese between 6 to10 years of age to remain obese in their adulthood.…”
mentioning
confidence: 99%
“…2 If left untreated, obesity-related comorbidities may develop in children at an early age that include sleep apnea, 3 cardiovascular disease risk factors, 4 type 2 diabetes, 5 and mental health issues. 6 Additional evidence suggests that it is highly likely that obese children will carry their excess weight into adulthood and thus have an increased risk of becoming obese adults in the absence of intervention. 7 It has been demonstrated that obese children have poorer maximal cardiorespiratory fitness levels than their normal weight peers, given the increased effort required to move a larger mass.…”
Section: Introductionmentioning
confidence: 99%